2008
DOI: 10.1016/j.orl.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of single machine scheduling problems under scenario-based uncertainty

Abstract: RésuméNous considérons des problèmes d'ordonnancement où certains paramètres des tâches sont incertains. Cette incertitude est modélisée au travers d'un ensemble fini de scénarios bien définis. Nous cherchons une solution qui soit acceptable pour l'ensemble des scénarios considérés. Plusieurs critères ont été utilisés dans la littérature pour sélectionner la "meilleure" solution. Nous utilisons ici le critère appelé robustesse absolue. Nous présentons des résultats algorithmiques et de complexité pour quelques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 8 publications
0
43
0
Order By: Relevance
“…Let p 1 = 3, p 2 = 1, p 3 = 2,p 1 = 1,p 2 = 10,p 3 = 5. By definition we have U Γ p = {(3, 1, 2), (4, 1, 2), (3,11,2), (3, 1, 7)}. Notice that a schedule is completely caracterized by a permutation of the job.…”
Section: Example For 1||umentioning
confidence: 99%
See 2 more Smart Citations
“…Let p 1 = 3, p 2 = 1, p 3 = 2,p 1 = 1,p 2 = 10,p 3 = 5. By definition we have U Γ p = {(3, 1, 2), (4, 1, 2), (3,11,2), (3, 1, 7)}. Notice that a schedule is completely caracterized by a permutation of the job.…”
Section: Example For 1||umentioning
confidence: 99%
“…We prove that 1||U Γ p | C j is polynomial by extending Theorem 1. Comparing with [2,6,23], the result illustrates how U Γ -robust scheduling can lead to more tractable problems than robust scheduling with arbitrary uncertainty sets. We show then that 1||U Γ p | w j C j is weakly N P-hard if Γ = 1 and strongly N P-hard if Γ > 1.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…de Farias et al (2010) identify a family of valid inequalities to strengthen the mixed-integer formulation of their problem. Furthermore, Aloulou and Croce (2008) provide several complexity results in the domain of robust single-machine scheduling. There also exist a few recent papers that propose scenario-based models for scheduling problems with multiple machines (see, e.g., Alonso-Ayuso et al, 2007;Kasperski et al, 2012); however, these also rely on risk-neutral or robust approaches.…”
Section: Machine Scheduling Under Uncertaintymentioning
confidence: 99%
“…Yang and Yu (2002) showed that a min-max version of the same problem is NP-hard and presented a dynamic programming method and two heuristic algorithms where min-max version minimizes maximum cost over all scenarios. Aloulou and Croce (2008) considered a min-max version of the single-machine scheduling problem with uncertain due dates, weights, and processing times. The performance measures considered were total weighted completion times, the general maximum cost function, and the number of late jobs.…”
Section: Literature Reviewmentioning
confidence: 99%